Strategi Inovatif Pengelolaan Terbitan Berseri Berbasis Digital di UPT Perpustakaan UIN Imam Bonjol Padang: Studi Kasus Menuju Transformasi Layanan Informasi - Muhammad Rizky (Maktabatuna, 2025)
The library is one of the important institutions in supporting education and research, especially in higher education. UPT Library UIN Imam Bonjol Padang has a strategic role as an academic information center, providing relevant reading materials for students, lecturers, and researchers. One of the important collections supporting scientific activities is serial publications, such as journals, magazines, bulletins, and annual reports, which are published periodically with continuously updated information. This study analyzes the management of serial publication collections at UPT Library UIN Imam Bonjol Padang. The management of serial publication collections is one of the important elements in improving information services for library users. This study uses a qualitative approach with a descriptive method to describe the management process that includes selection, acquisition, processing, preservation, and dissemination of serial publication collections. The results of the study indicate that UPT Library UIN Imam Bonjol Padang has implemented management steps per library standards, although there are several obstacles such as limited human resources and supporting technology. The proposed solutions include staff capacity development, improving technology infrastructure, and optimizing cooperation with publishers. Thus, the management of serial publication collections can be more effective and provide maximum benefits for the academic community.